Modal salient belief and social cognitive variables of anti-doping behaviors in sport: Examining an extended model of the theory of planned behavior. (January 2015) - Chan, Derwin King Chung; Hardcastle, Sarah; Dimmock, James A.; Lentillon-Kaestner, Vanessa; Donovan, Robert J.; Burgin, Matthew; Hagger, Martin S.
Abstract: Objectives: This study examined the modal salient behavioral, normative, and control beliefs within the theory of planned behavior (TPB) in the context of anti-doping in sport. We tested the efficacy of four hypothesized expectancy-value models as predictors of the directly-measured social-cognitive components of the TPB toward doping avoidance: attitude, subjective norm, perceived behavioral control (PBC), and intention. Methods: After developing the belief-expectancy and belief-value of modal salient beliefs items based on a pilot belief-elicitation study of young elite athletes ( N  = 57, mean age = 18.02), 410 young athletes (mean age = 17.70) completed questionnaire items of the modal salient beliefs and direct measures of the social-cognitive components of doping avoidance. Variance-based structural equation modeling was used to examine the four proposed expectancy-value models. Results: Belief-expectancies, belief-values, and the expectancy-belief multiplicative composites formed positive associations with their corresponding social cognitive variables. The model in which belief-expectancies were the sole predictors of the social cognitive provided the most parsimonious and reliable model to explain the relationship between modal salient beliefs and directly-measured social-cognitive variables for doping avoidance in sport. Conclusion: Belief-expectancies including behavioral belief strength (e.g., "doping avoidance is likely to ease the worry of being caught doping"), normative belief strength ("my coach thinks that I should avoid doping") and control belief strength ("I expect I have power to 'say no' to doping") are the belief-based components that underpin direct measures of the social-cognitive variables from the TPB with respect to doping avoidance. Highlights: This study applied the theory of planned behavior in an anti-doping context. Attitude did not significantly predict intention of doping avoidance. Subjective norm and perceived behavioral control were positive correlates of intention. The results also supported the expectancy-value model. Belief expectancies estimated the social cognitive factors of anti-doping.